Pendugaan Parameter Genetik dan Seleksi Karakter Morfofisiologi Galur Jagung Introduksi di Lingkungan Tanah Masam - Lubis, Khairunnisa; Sutjahjo, Surjono Hadi; Syukur, Muhamad; Trikoesoemaningtyas, Trikoesoemaningtyas (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
Morpho-physiological characterization of sixteen inbred lines of maize originated from CIMMYT and from Indonesian Cereals Research Institute Maros, was carried out in Tenjo, Bogor, from January to April 2013. The objectives of this research were to (1) estimate the genetic parameters of morphophysiological characters, (2) obtain morpho-physiological characters that can be used as selection characters and (3) obtain tolerance inbred lines on acid soil condition. The experiment was conducted using a Nested Design with three replications, nested in selection environment. The first factor was environments, the second factor was genotypes. The two environments were acid soil with eAl 0.2 me/100 g (represented the optimum soil) and acid soil with eAl 1.87 me/100 g (represented the medium acid soil). The results showed that environment had significant effect on inbred lines performances. Characters of anthesis silk interval, number of seeds/cob, number of rows/cob, cob dry weight, seed dry weight and cob weight/plot could be used as selection characters for tolerance to medium acid soil condition; the inbred lines tested indicated high genetic variabilities and showed high heritability under such condition. Inbred line CLA 84, CLA 46, CLA 95 and 1042-13 each was found tolerant genotype on medium acid soil condition